(untitled) (Strathmore Law Review, 2017)
A national budget needs funding with the sources being either domestic or foreign. Foreign sources of funding seem to dominate the Kenyan context. This paper argues that a country with a national budget dependent on foreign aid can be held hostage by the holders of the purse strings. Further, that this dependency has a negative impact on Kenya’s economic sovereignty. It is this impact that is of relevance to this paper. In this spirit the paper critically analyses Kenya’s borrowing trend with a special focus on foreign aid, defines by use of a working definition the importance of economic sovereignty, explores how this borrowing trend affects Kenya’s economic sovereignty and offers solutions on regaining of Kenya’s economic sovereignty.